Political media and political globalization Convergence and correlation - Rahim Al - Azzawi, Dr. Haitham Nima (al-Ustādh, 2018)
The present world is witnessing strong structural indicators that reflect the interrelationship between political media and political globalization. This research presents a correlation between the two concepts and the extent of their influence on each other. The most important political media trends and their impact on the global discourse and its impact on it. In three research, introduction and conclusion,.        The second topic dealt with the concept of political media, relying on media systems and different media theories, and the embodiment of the relationship between politics and media through the role of the means of communication in strengthening political participation. Globalization and political strife towards it through the search for the essence of globalization and the mystery of its vagueness in some fields, I ask God that I have earned it and be useful, and my sense that I am a sinner and harm and perfection to the owner of perfection Glory and Glory be to God and Muhammad and J all and companions of all.. And God reconcile.